Testing Bench for Reciprocating Hydraulic Cylinders with Energy Recovery: Structure, Simulation, and Calculation - A. R. Zenin; A. T. Rybak; A. N. Beskopylny; A. Yu. Pelipenko; Yu. A. Serdyukova (Advanced Engineering Research)
Introduction. Energy conservation is an urgent topic of research in the field of mechanical engineering all over the world. A particular direction in these studies is the search for energy-efficient methods of testing technical systems, which allow the most accurate prediction of the reliability of the designed equipment. The duration of resource tests established by technical conditions and GOSTs causes an irreversible loss of energy, amounting to more than 1.5 resource of the tested machine, and the energy lost in the form of “harmful heat” is released into the environment. Therefore, the problem of energy saving during testing is given special attention. One of the ways of energy saving under testing of hydraulic machines is energy recovery. However, in papers devoted to energy recovery during testing of hydraulic machines, the problems of energy recovery during testing of rotary hydraulic machines were solved, and for reciprocating hydraulic machines, the problem of energy recovery during testing of plunger hydraulic cylinders was solved. The results of these studies cannot be directly used for testing reciprocating hydraulic cylinders. In this regard, the objective of this work has been formulated — to develop the structure and basic scheme of a test bench for reciprocating hydraulic cylinders, providing the recovery of part of the energy spent on testing, due to which the energy efficiency of the testing process is significantly increased.Materials and Methods. The paper used methods for modeling the process of stand functioning based on the application of the theory of volumetric rigidity. To carry out preliminary calculations of the stand operation process, a computer program based on the SimInTech software package was developed.Results. A structural and schematic diagram of a test bench for reciprocating hydraulic cylinders has been developed. A mathematical expression has been obtained that provides a preliminary assessment of the test efficiency coefficient. A computer program based on the SimInTech software package has been created, which allows the design parameters of the stand affect its operational characteristics, including the coefficient of energy efficiency of the test process.Discussion and Conclusion. The preliminary calculations of the operating characteristics of the stand showed that the efficiency coefficient of the proposed stand was 1.7. It can be increased by conducting additional studies aimed at obtaining rational design parameters of the stand. The proposed stand provides testing of reciprocating hydraulic cylinders with recovery of part of the expended energy, and its mathematical model allows using the numerical methods in calculations. This significantly simplifies the calculation process and increases the accuracy of the calculations. At the same time, it is possible to obtain rational parameters of the stand already at the design stage, without resorting to expensive and labor-intensive field studies.